Mathematical Modeling of Coronavirus Dynamics with Conformable Derivative in Liouville–Caputo Sense - Ebenezer Bonyah; Zakia Hammouch; Mehmet Emir Koksal (Journal of Mathematics)
Coronavirus has become a serious global phenomenon in recent times and has negative effects on the entire world economy. In this study, a fractional mathematical model formulated in fractional conformable derivative is studied. The model hinges on the concept of mammal hosts and humans. The basic properties of the coronavirus model are investigated. The stability analysis is carried out as well as sensitivity analysis based on the reproduction number. Numerical simulation is undertaken to give impetus to the analytical results which indicate that both fractional conformable order derivative and fractional-order derivative have serious consequences in numerical result outcomes.